The imminent competition preparation (ICP) in canoe sprint - Englert, M. (2009)
Content of the presentation: 1. Definitions and objectives 2. Training-methodical contents and tasks 3. The structural organization of the ICP 4. Examples of ICP organization 5. Comparison of framework training plans of the ICP of 2 Olympic Games 6. The importance of preparative competitions 7. Preparation for particularities of the location of the competition 8. Possible problems